Firm Size's Moderating Role in Financial Factors and Tax Avoidance: Peran Pemoderasi Ukuran Perusahaan terhadap Hubungan antara Faktor Keuangan dan Penghindaran Pajak: Bukti dari Sektor Industri Kimia dan Dasar di Indonesia - Dwi Nanningsih; Santi Rahma Dewi (Academia Open, 2023)
This study examines the influence of sales growth, leverage, and profitability on tax avoidance, while considering the moderating effect of firm size in the context of manufacturing companies in the Chemical and Basic Industry sector listed on the Indonesia Stock Exchange from 2017 to 2020. Using a quantitative research approach and purposive sampling method, data from 9 companies with 36 observations were analyzed through the Smart PLS 3.0 program. The findings indicate that firm size does not moderate the effects of sales growth and leverage on tax avoidance, but it does moderate the effect of profitability on tax avoidance. These results contribute to a better understanding of the complex relationship between financial factors and tax avoidance, emphasizing the significance of firm size as a moderating factor. This research has implications for policymakers, tax authorities, and practitioners seeking to devise strategies to enhance tax compliance and discourage tax avoidance practices within the Chemical and Basic Industry sector. Highlights: Firm size moderates profitability's impact on tax avoidance. Sales growth and leverage are not moderated by firm size. Study conducted on manufacturing companies in the Chemical industry. Keywords: Firm size, Financial factors, Tax avoidance, Chemical industry, Indonesia